Diseño e implementación de un horno eléctrico para el secado de motores en la empresa SIPROELECTRIK S.A. - Cumba Jaguaco, Byron Eduardo (2019)
In the development of maintenance systems of electrical machines, such as motors, transformers, generators there are certain processes that allowed to efficiently carry out the maintenance of the same, the engineering project was carried out in the Province of Pichincha, in La Armenia, in the company “SIPROELECTRICK S.A.”, in which a better process was required for the drying of the varnish in the engines and to replace the traditional processes that are currently handled in the company. The main purpose of this research was to design and implement an electric oven for drying engines, generators and transformers using technology existing in the market. The oven implemented was built with technological methods that helped to the control and optimization the drying time of the motors. The furnace was manufactured with electromechanical elements, where the heat provided its operation is based on electrical resistances whose power is 2000 W, each. Use of a pyrometer as a tool to maintain a stable temperature inside the oven, which is designed to reach a maximum temperature of 200 ° C, with a maximum engine load of 75 hp. The furnace has been implemented an OFF-DELAY timer to control the duration of drying of the engines optimizing the time of the process for the operator. With the implementation of this machine it was possible to control parameters mentioned above by means having a reduction of 20 minutes in the drying process and an optimization in the consumption of the electrical energy. It also achieves a safer and simpler process for the operator, achieved through the implementation of the control system through an easy to manipulate board.